Determining The Etiology of Uveitis in Indonesia: The Role of Clinical Manifestation and Serological Test in Infectious Uveitis - Anissa, Gisela Haza; Rina La Distia Nora (Majalah Oftalmologi Indonesia, 2025)
Introduction: Uveitis is a heterogeneous group of intraocular diseases that significantly causes vision disabilities in patients worldwide. Establishing an etiological diagnosis can be challenging because of the extensive and varied clinical patterns and differential diagnoses across regions. Knowledge of these patterns is crucial in aiding physicians with diagnosis, reducing the need for costly ancillary tests, and facilitating timely management.   Methods: We conducted a retrospective descriptive study using medical records data from a tertiary referral hospital in Indonesia over two years (2016-2017), involving 299 patients with uveitis.   Discussion: Among the 299 patients, 152 were men (152/299, 50.8%) with a median age of 36. Panuveitis was the most frequent anatomical entity (152/199, 53.2%). Infectious etiology, primarily toxoplasmosis and tuberculosis, remained prevalent. Despite various final diagnoses, serological tests for IgG Toxoplasma and CMV were predominantly reactive in 192/251 (76.5%) and 228/236 (96.6%) of tested patients. At presentation, 106/299 (35%) of patients were categorized as blind, and 64/106 (60%) were without improvement. Complications were observed in 167/299 (55%) of patients, including cataracts (133/299, 44%) and glaucoma (32/299, 10%), contributing to 70/106 (66%) of blindness in our series.   Conclusion: Panuveitis and infectious etiology, particularly toxoplasmosis and tuberculosis, were the most common causes of uveitis. Clinical patterns were better able to distinguish them than laboratory results. Understanding these uveitis patterns can guide physicians in diagnosing before performing expensive ancillary tests. Ocular complications were related to severe visual function; thus, timely referral in severe cases is essential.   Keywords: Uveitis, Indonesia, epidemiology